Virtual Reality Interventions of Daily Versus Weekly Data Collection in Patient-Reported Outcomes Among Adults With Cancer: Pilot Survey Study - Matthew Browning; Olivia McAnirlin; Fu Li; Jeffrey Bertrand; Denise Davis; Kapil Madathil; George Fredric Mau; Teny Henry Gomez (JMIR Formative Research)
Abstract BackgroundVirtual reality (VR) interventions are increasingly used in health care settings to improve patient-reported outcomes (PROs). PROs are commonly evaluated at weekly intervals with data collected via digital surveys. While weekly assessments have benefits, VR devices enable more frequent in-device data collection. It remains unclear whether PROs collected more frequently provide more information on these interventions than PROs collected more infrequently. ObjectiveThis pilot study explored differences between daily and weekly PRO data collection in a VR intervention with nature imagery, with and without guided imagery, among patients with cancer. MethodsPatients with cancer (n=8) were randomly assigned to one of four intervention groups: (1) virtual reality–assisted guided imagery (VRAGI), (2) VR without guided imagery, (3) desktop VR with guided imagery, or (4) desktop VR without guided imagery. Devices were mailed to participants’ homes for 15‐20 minutes of daily use over 3 weeks. Weekly outcomes (pain, anxiety, depression, and well-being) were assessed using items from the Edmonton Symptom Assessment Scale. Daily outcomes were captured via in-device pre-post surveys. Data were analyzed descriptively, using visual trend comparisons to explore patterns. ResultsOf 41 patients who consented, 8 provided complete and usable data. Weekly outcomes showed no consistent trends. In contrast, daily data revealed more nuanced patterns, such as early symptom relief, plateaus, and “double-bottom” effects. The addition of guided imagery did not consistently enhance outcomes beyond VR alone, although the VRAGI condition showed the greatest improvement in well-being. Given the small sample size, these findings should be considered exploratory. ConclusionsThis pilot study suggests that daily PRO data might offer richer insight into intervention effects than weekly assessments. Further research with larger samples is needed to confirm these patterns.